Research progress of electronic nose on identification of food adulteration - ZHANG Gui-yun; XIE Jian-hua; YANG Wei-qiang (Shipin yu jixie, 2023)
This paper introduces the working principle of electronic nose via two key elements including gas sensor array and signal processing. The applications of electronic nose in adulteration identification and quality analysis of edible oil, dairy products, beverage, meat, spices, and other foods are reviewed. The operations and analytical principle of electronic nose for food adulteration are clarified, and the successful applications of electronic nose as well as the shortcomings are discussed.